Symposium 2: The Power of Theory: An Actor-Network Critique of Aha! Moments and Doctoral Learner Empowerment - Keefer, Jeffrey M. (Proceedings of the International Conference on Networked Learning, 2014)
Doctoral studies can be envisioned as a journey to prepare novice researchers or expert practitioners to produce an original contribution to a field or engage in disciplinary stewardship. The focus is often upon the individual’s individuality in production, and not about challenges or supports encountered along the way that lead to those achievements. Many postgraduates struggle in achieving these contributions, and while sometimes they are rather public in nature, quite often they involve private battles that are confronted and won, or lost, in solitude. However, stewardship and originality do not necessitate isolation, and in the same way that ideas commonly generate in reaction and relation to other ideas, so too does the role of support structures within doctoral studies when they are most needed. While other people in the lives of the doctoral learner—supervisors, friends, family—are readily recognized as the support network, less is known about the network of things, especially the influential role that theory plays, in the lives of postgraduates. It is this very theory that has the power to help the learner work through the troublesome periods en route to achieving the doctorate. This study engaged an actor-network critique of the power of theory in the lives of doctoral students to explore how the notion of translation can provide insights into understanding how liminal periods, those challenging times where one is no longer the initiate but not yet the expert in one’s field or discipline, can be resolved (Kiley, 2009). Using Callon’s (1986) four-part schema of translation—problematization, interessement, enrolment, and mobilization—the role of theory in doctoral learning was examined within the context of a study of 23 international and interdisciplinary doctoral learners to better understand how theory itself exhibited power to support the journey through troublesome periods when no other support was available or strong enough to suffice. The result was the experience of aha! moments of theoretical clarity and appreciation, with an unexpected power for these non-human actors to resolve the liminal periods and support postgraduates with confidence as they completed their journeys.